Compounding effects of adult ADHD and comorbidities on intimate relationships - Anh-Luu T; Sara Benowitz (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Although research about adult Attention Deficit Hyperactivity Disorder (adult ADHD) has become more prevalent since the condition's recognition in the 1990s, information remains scarce about if and how its psychiatric comorbidities may compound impact on functionality in relationships. Studies abound on the independent effects on relationships of two of adult ADHD's most common comorbidities - mood and substance use disorders. However, adults with ADHD sans comorbidities often experience interpersonal relationship difficulties due to the disorder's signature symptoms alone - hyperactivity, impulsivity, and inattentiveness - as well as due to adult ADHD's oft-observed dimension of emotional lability. The primary purpose of this study is to review the literature regarding the impact on intimate relationships of adult ADHD, as well as look at the potential compounding effects of comorbid mood or substance use disorder. The secondary purpose of this paper is to examine the literature on integrative therapy to treat couples wherein at least one partner struggles with adult ADHD, with or without comorbidities. Future research and practice implications are also discussed, including the hope for focus on the positive aspects of ADHD for individuals and relationships.